The role of circadian clock in astrocytes: From cellular functions to ischemic stroke therapeutic targets - Zhang, Yuxing; Zhao, Xin; Zhang, Ying; Zeng, Fukang; Yan, Siyang; Chen, Yao; Li, Zhong; Zhou, Desheng; Liu, Lijuan (Frontiers in Neuroscience, 2022)
Accumulating evidence suggests that astrocytes, the most abundant cell type in the central nervous system (CNS), play a critical role in maintaining the immune response after cerebral infarction, the blood-brain barrier (BBB) and Functions such as neurotoxicity. The circadian clock is an endogenous timing system that controls and optimizes biological processes. The central circadian clock and the peripheral clock are consistent, controlled by various circadian components, and participate in the pathophysiological process of astrocytes. Existing evidence shows that circadian rhythm controls the regulation of inflammatory responses by astrocytes in ischemic stroke, regulates the repair of the blood-brain barrier, and play an essential role in a series of pathological processes such as neurotoxicity. This study reviewed the mechanism of circadian rhythm regulation of astrocytes at the molecular level and its contribution to functional recovery after ischemic stroke. A comprehensive understanding of the ability of the circadian clock to regulate astrocytes after stroke is expected to develop new therapeutic strategies for the treatment of ischemic stroke.